Synthesis and physical properties of (Zr1−x, Tix)3AlC2 MAX phases. Issue 8 (21st April 2017) - Zapata‐Solvas, Eugenio; Hadi, Mohammad A.; Horlait, Denis; Parfitt, David C.; Thibaud, Axel; Chroneos, Alexander; Lee, William E.
Abstract: MAX phase solid solutions physical and mechanical properties may be tuned via changes in composition, giving them a range of possible technical applications. In the present study, we extend the MAX phase family by synthesizing (Zr1− x Ti x )3 AlC2 quaternary MAX phases and investigating their mechanical properties using density functional theory (DFT). The experimentally determined lattice parameters are in good agreement with the lattice parameters derived by DFT and deviate <0.5% from Vegard's law. Ti3 AlC2 has a higher Vickers hardness as compared to Zr3 AlC2, in agreement with the available experimental data.